Pengorganisasian Administrasi Pendidikan - Fadya Safitri Rahman; Armilah Armilah; Tiara Ramadhani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Organizing as a process of determining, grouping and arranging various activities needed To achieve goals, determining authority that is relatively delegated to each individual who will Carry out these activities. Organizing as a process of dividing work into smaller tasks, assigning These tasks to people according to their abilities, and allocating resources and coordinating them In order to effectively achieve organizational goals. The research method used in this research is Library research, which is a way to collect data by understanding and studying theories from various Literature related to the research topic. An organization, of course, will never become big if its Members only think that their existence in the organization is only based on the same fate.